The effect of smoking on post-operative finger range of motion in patients with tendon grafts - Justan, Ivan; Ovesná, Petra; Kubek, Tomáš; Hýža, Petr; Stupka, Igor; Dvořák, Zdeněk (In Vivo, 2011)
BACKGROUND: The finger range of motion (ROM) was evaluated in patients with hand flexor tendon replacement using a tendon graft and the effect of smoking was investigated. The first hypothesis was: a tendon graft increases the post-operative ROM. The second hypothesis was: smoking has a negative effect on the final finger ROM. PATIENTS AND METHODS: Fifty seven autologous tendon grafts in 48 patients were included. The patients were grouped as non-smokers or smokers ("light" or "heavy"). The modified Strickland system and Total Active Motion (TAM) system, were chosen for the evaluation. RESULTS: The first hypothesis was proved by all the measurements. The post-operative status assessed by the Strickland method was different between the non-smokers and smokers with a better score in the smokers. CONCLUSION: A significant ROM improvement occurs after reconstruction and is even slightly better in smokers than in non-smokers.
Keywords: terapie cvičením; Smoking; poranění šlachy; Postoperative Period; pooperační období; šlachy; Range of Motion, Articular; Tendons; Tendon Injuries; Transplants; transplantáty; lidé; prsty ruky; rozsah kloubních pohybů; Fingers; kouření; Humans; Exercise Therapy